An Improved Iodine-Catalyzed Aromatization Reaction and Its Application in the Synthesis of a Key Intermediate of Cannabidiol - Abduahadi, Safomuddin; Mintah Bonku, Emmanuel; Qin, Hongjian; Odilov, Abdullajon; Zhu, Fuqiang; Aisa, Haji Akber; Shen, Jingshan (Synlett, 2024)
In this study, the development of an improved process for the synthesis of a key cannabidiol intermediate, methyl olivetolate, is described. The process involves an improvement of the iodine-catalyzed aromatization of cyclohexanone using potassium persulfate as an oxidant. This approach enabled for the efficient synthesis of methyl olivetolate with a 90% yield and 99.84% HPLC purity on a 5 kg scale. Additionally, a total of 19 cyclohexanone substrates afforded higher yields (71–92%) of m-diphenol compounds compared to the established methods.
Keywords: methyl olivetolate; potassium persulfate; aromatization; oxidation; iodine-catalyst; cannabidiol